The Fbn1 gene variant governs passive ascending aortic mechanics in the mgΔlpn mouse model of Marfan syndrome when superimposed to perlecan haploinsufficiency - Samar A. Tarraf; Rodrigo Barbosa de Souza; Ashley Herrick; Lygia V. Pereira; Chiara Bellini (Frontiers in Cardiovascular Medicine, 2024)
IntroductionAscending thoracic aortic aneurysms arise from pathological tissue remodeling that leads to abnormal wall dilation and increases the risk of fatal dissection/rupture. Large variability in disease manifestations across family members who carry a causative genetic variant for thoracic aortic aneurysms suggests that genetic modifiers may exacerbate clinical outcomes. Decreased perlecan expression in the aorta of mgΔlpn mice with severe Marfan syndrome phenotype advocates for exploring perlecan-encoding Hspg2 as a candidate modifier gene.MethodsTo determine the effect of concurrent Hspg2 and Fbn1 mutations on the progression of thoracic aortopathy, we characterized the microstructure and passive mechanical response of the ascending thoracic aorta in female mice of four genetic backgrounds: wild-type, heterozygous with a mutation in the Fbn1 gene (mgΔlpn), heterozygous with a mutation in the Hspg2 gene (Hspg2+/−), and double mutants carrying both the Fbn1 and Hspg2 variants (dMut).ResultsElastic fiber fragmentation and medial disarray progress from the internal elastic lamina outward as the ascending thoracic aorta dilates in mgΔlpn and dMut mice. Concurrent increase in total collagen content relative to elastin reduces energy storage capacity and cyclic distensibility of aortic tissues from mice that carry the Fbn1 variant. Inherent circumferential tissue stiffening strongly correlates with the severity of aortic dilatation in mgΔlpn and dMut mice. Perlecan haploinsufficiency superimposed to the mgΔlpn mutation curbs the viability of dMut mice, increases the occurrence of aortic enlargement, and reduces the axial stretch in aortic tissues.DiscussionOverall, our findings show that dMut mice are more vulnerable than mgΔlpn mice without an Hspg2 mutation, yet later endpoints and additional structural and functional readouts are needed to identify causative mechanisms.